Reproductive ability of black currant cultivars after pollen cryopreservation in liquid nitrogen - O. A. Tikhonova; E. A. Radchenko; A. V. Pavlov (Труды по прикладной ботанике, генетике и селекции)
Background. Studying the reproductive ability of black currant cultivars after long-term cryopreservation of their pollen in liquid nitrogen is very important for plant diversity conservation and for the effectiveness of breeding efforts.Materials and methods. Five black currant cultivars served as the material for the research. The viability of black currant pollen after cryopreservation in liquid nitrogen was analyzed. Pollen viability was tested on an artificial medium containing 10% of sucrose and 0.8% of agar. The viability of pollen was tested on the black currant collection at Pushkin and Pavlovsk Laboratories of VIR. The cultivar ‘Andreevskaya’ (k-15630) was pollinated with pollen stored for one year in liquid nitrogen (–196°C) as well as with fresh pollen (control test).Results and conclusion. After 12 months of conservation under ultralow temperatures there was a change in the level of pollen viability depending on the genotype: it varied from 10.4% (cv. ‘Pozdnyaya poslevoennaya’, k-7654) to 50.4% (cv. ‘Kriviai’, k-42517), while its mean value was 0.9% higher than the mean initial viability. The fruit setting rate in the control option was 81.3–94.2%. When pollinated with pollen kept in liquid nitrogen for one year, the fruit setting rate varied from 69.2% (‘Kacha’, k-44185) to 93.3% (‘Belorusochka’, k-41978); the remaining cultivars (‘Pozdnyaya poslevoennaya’; ‘Chereshneva’, k-42481; and ‘Kriviai’) demonstrated intermediate values of this indicator, i.e., the reproductive ability of pollen after cryopreservation was high even despite its low viability. As for the fruit weight, no differences were shown by cvs. ‘Kacha’, ‘Chereshneva’ and ‘Kriviai’ in both pollination options, while this indicator in cvs. ‘Belorusochka’ and ‘Pozdnyaya poslevoennaya’ was lower than the control by 0.31 and 0.24 g, respectively.